2020
DOI: 10.7150/ijbs.47595
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Plays an Important Role by Influencing NLRP3 inflammasome

Abstract: Inflammasome is a complex composed of several proteins and an important part of the natural immune system. Nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome is composed of NLRP3, apoptosis associated speck like protein (ASC) and pro-caspase-1. It plays an important role in many diseases. Hydrogen sulfide (H 2 S) is an important signaling molecule that regulates many physiological and pathological processes. Recent studies indicated that H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 101 publications
1
16
0
Order By: Relevance
“…In recent years, the interaction between autophagy and NLRP3 inflammasome has been reported to be involved in many metabolic disorder-related diseases, including NAFLD [ 8 ]. Moreover, NLRP3 inflammasome can be used as a target of H 2 S regulation in many diseases [ 21 ]. Therefore, whether H 2 S can improve NAFLD by regulating autophagy/NLRP3 inflammasome is a topic worthy of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the interaction between autophagy and NLRP3 inflammasome has been reported to be involved in many metabolic disorder-related diseases, including NAFLD [ 8 ]. Moreover, NLRP3 inflammasome can be used as a target of H 2 S regulation in many diseases [ 21 ]. Therefore, whether H 2 S can improve NAFLD by regulating autophagy/NLRP3 inflammasome is a topic worthy of study.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, hydrogen sulfide(H 2 S) has been regarded as a toxic gas. However, since the 1990s, more and more studies have demonstrated that H 2 S, together with NO and CO, is gas transmission signal molecules [ 21 , 22 ].There are three enzymes that catalyze the production of endogenous H 2 S: cystine sulfide β-synthase (CBS), cystine sulfide γ-lyase (CSE), and 3-mercaptopyruvate sulfur transferase (3-MST). CBS catalyzes the β-substitution reaction of homocysteine with serine to produce L-cystathionine.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy, the NLRP3 inflammasome, and ERS are the regulated targets of H 2 S and are involved in the process of improving DCM by H 2 S, so the interaction among the three in H 2 S improvement of DCM should be studied in the future. ERS and NLRP3 inflammasome crosstalk has been reported to play an important role in metabolic disorders (Ji et al, 2019 ), and H 2 S regulates the ERS/NLRP3 inflammasome in many diseases (Wang et al, 2020a , b ), so whether H 2 S can regulate the ERS/NLRP3 inflammasome to improve diabetes deserves to be studied. In addition, the existing H 2 S releasers cannot fully meet the requirements of research and development of H 2 S related drugs, so the development of new H 2 S releasers is very important for the application of H 2 S related drugs in the treatment of clinical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, H 2 S has been considered to be a toxic and odorous gas. However, since the 1990s, many studies have shown that H 2 S, along with NO and CO, belongs to the category of gasotransmitters (Wang et al, 2020b ). Three “classic” H 2 S-producing enzymes have been identified: cystathionine-γ-lyase (CSE), cystathionine-β-synthase (CBS), and 3-mercaptopyruvate thiotransferase (3-MST) (Rose et al, 2017 ).…”
Section: Overview Of H 2 Smentioning
confidence: 99%
“…Aminotransferase catalyzes cystine to transfer amine to α- Ketoglutarate to form 3-mercaptopyruvic acid (3-MP). The sulfur of 3-MP was catalyzes by 3-MST to convert into H 2 S ( Wang et al, 2020 ; Figure 2 ). It has been reported that H 2 S plays an important biological role in many human systems, such as respiratory system, cardiovascular system, endocrine system, nervous system, immune system, and gastrointestinal system ( Gotor et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%